2018
DOI: 10.1101/508051
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prefrontal pathways provide top down control of memory for sequences of events

Abstract: 38We remember our lives as sequences of events, but it is unclear how these memories are controlled 39 during retrieval. In rats, prelimbic cortex (PL) is positioned to influence sequence memory through 40 extensive top down inputs to the nucleus reuniens of the thalamus (RE) and perirhinal cortex (PER), 41 regions heavily interconnected with the hippocampus. Here, we tested the hypothesis that specific 42 PL→RE and PL→PER projections regulate sequence memory retrieval using an hM4Di synaptic-silencing 43 appr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 79 publications
0
24
0
Order By: Relevance
“…Although little is known about the role of RE in sequence memory, a recent report tested the hypothesis that RE is critical to remembering sequences of events in rats ( Fig. 6; Jayachandran et al 2018). In this study, rats were trained on an odor-based sequence memory task in which they had to identify odors as "in sequence" or "out of sequence" for water rewards.…”
Section: Re In the Temporal Organization Of Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…Although little is known about the role of RE in sequence memory, a recent report tested the hypothesis that RE is critical to remembering sequences of events in rats ( Fig. 6; Jayachandran et al 2018). In this study, rats were trained on an odor-based sequence memory task in which they had to identify odors as "in sequence" or "out of sequence" for water rewards.…”
Section: Re In the Temporal Organization Of Memorymentioning
confidence: 99%
“…Through a detailed lag analysis, Jayachandran et al (2018) revealed a pattern of deficits that resembled a reduction in a working memory retrieval strategy after silencing the mPFC → RE pathway, in contrast to a temporal context memory retrieval strategy, which was instead impaired by silencing mPFC → PRC. To clarify this issue, temporal context memory in the sequence task refers to the retrieval gradients that are observed in human studies of list learning (e.g., Howard and Kahana 2002;Kragel et al 2015).…”
Section: Re In the Temporal Organization Of Memorymentioning
confidence: 99%
“…In addition, NRe and HPC EPSPs show equal rise time (NRe 3.6 ± 0.3 ms, HPC 3.7 ± 0.3 ms) indicating equal distance from the soma (Sjostrom & Hausser 2006). associative recognition memory (Barker & Warburton 2018) and sequence memory (Jayachandran et al 2019), but the circuit mechanisms underlying these functions are not understood. Whilst the behavioural function of the associative plasticity we describe remains to be determined, the specific timing conditions for plasticity we report suggest that NRe may impose a timing control which determines the salience of HPC signals and promotes their encoding.…”
Section: Input-timing Dependent Plasticity Of Nre and Hpc Synapsesmentioning
confidence: 99%
“…In support of this interpretation, prefrontal cortical neuron spiking increases coordinated activity between perirhinal and lateral entorhinal cortices (Paz et al, 2007), which could facilitate cortical-hippocampal interactions. Conversely, blocking prefrontal neural activity or prefrontal-perirhinal communication impairs the ability to retrieve previously learned hippocampal-dependent object-place associations (Hernandez et al, 2017) and odor sequence memories (Jayachandran et al, 2019). Activation of prefrontal neuronal ensembles that receive synaptic input from the perirhinal cortex is attenuated in aged rats when tested in a hippocampaldependent object-place association task (Hernandez et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%